Different roles of astrocytes in the blood–brain barrier during the acute and recovery phases of stroke - Jialin Cheng; Yuxiao Zheng; Fafeng Cheng; Chunyu Wang; Jinhua Han; Haojia Zhang; Xin Lan; Chuxin Zhang; Xueqian Wang; Qingguo Wang; Changxiang Li (Neural Regeneration Research, 2026)
Ischemic stroke, a frequently occurring form of stroke, is caused by obstruction of cerebral blood flow, which leads to ischemia, hypoxia, and necrosis of local brain tissue. After ischemic stroke, both astrocytes and the blood–brain barrier undergo morphological and functional transformations. However, the interplay between astrocytes and the blood–brain barrier has received less attention. This comprehensive review explores the physiological and pathological morphological and functional changes in astrocytes and the blood–brain barrier in ischemic stroke. Post-stroke, the structure of endothelial cells and peripheral cells undergoes alterations, causing disruption of the blood–brain barrier. This disruption allows various pro-inflammatory factors and chemokines to cross the blood–brain barrier. Simultaneously, astrocytes swell and primarily adopt two phenotypic states: A1 and A2, which exhibit different roles at different stages of ischemic stroke. During the acute phase, A1 reactive astrocytes secrete vascular endothelial growth factor, matrix metalloproteinases, lipid carrier protein-2, and other cytokines, exacerbating damage to endothelial cells and tight junctions. Conversely, A2 reactive astrocytes produce pentraxin 3, Sonic hedgehog, angiopoietin-1, and other protective factors for endothelial cells. Furthermore, astrocytes indirectly influence blood–brain barrier permeability through ferroptosis and exosomes. In the middle and late (recovery) stages of ischemic stroke, A1 and A2 astrocytes show different effects on glial scar formation. A1 astrocytes promote glial scar formation and inhibit axon growth via glial fibrillary acidic protein, chondroitin sulfate proteoglycans, and transforming growth factor-β. In contrast, A2 astrocytes facilitate axon growth through platelet-derived growth factor, playing a crucial role in vascular remodeling. Therefore, enhancing our understanding of the pathological changes and interactions between astrocytes and the blood–brain barrier is a vital therapeutic target for preventing further brain damage in acute stroke. These insights may pave the way for innovative therapeutic strategies for ischemic stroke.